2006
DOI: 10.1107/s1744309106004660
|View full text |Cite
|
Sign up to set email alerts
|

Purification, crystallization and preliminary characterization of a putative LmbE-like deacetylase fromBacillus cereus

Abstract: The Bacillus cereus BC1534 protein, a putative deacetylase from the LmbE family, has been purified to homogeneity and crystallized using the hanging-drop vapour-diffusion method. Crystals of the 26 kDa protein grown from MPD and acetate buffer belong to space group R32, with unit-cell parameters a = b = 76.7, c = 410.5 Å (in the hexagonal setting). A complete native data set was collected to a resolution of 2.5 Å from a single cryoprotected crystal using synchrotron radiation. As BC1534 shows significant seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
2
0

Year Published

2007
2007
2010
2010

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 11 publications
3
2
0
Order By: Relevance
“…5A). The positions of these bands are in agreement with the molecular mass of purified BC1534 estimated by size‐exclusion chromatography [13] and glutaraldehyde cross‐linking [18] (approximately 160 kDa), indicating that the protein exists as a hexamer in solution.…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…5A). The positions of these bands are in agreement with the molecular mass of purified BC1534 estimated by size‐exclusion chromatography [13] and glutaraldehyde cross‐linking [18] (approximately 160 kDa), indicating that the protein exists as a hexamer in solution.…”
Section: Resultssupporting
confidence: 77%
“…In the crystal, the protein forms a compact hexamer (Fig. 3A), in agreement with solution data [13]. A zinc binding site and a potential active site have been identified in each monomer.…”
Section: Introductionsupporting
confidence: 82%
“…These values indicate a significant stabilization upon hexamerization. In agreement with the crystal structure, gel filtration experiments have shown that the enzyme elutes as a single peak to a volume that is consistent with a spherical hexamer [17]. These results for Bc ZBP are consistent with an ultracentrifugation analysis of TT1542 [7], which also indicate a hexameric assembly.…”
Section: Resultssupporting
confidence: 75%
“…The expression, purification and crystallization of Bc ZBP have been reported previously [17]. High resolution diffraction data were collected from a single frozen crystal (100 K) using beamline X12 at the European Molecular Biology Laboratory/Deutsches Elektronen‐Synchrotron (Hamburg, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…Part of this interest was subsequently transferred to more benign, but still closely related to B. anthracis , species like B. cereus , an opportunistic bacterium causing food poisoning . In a drive to characterize, both functionally and structurally, deacetylases that are shared between these two organisms (and which may be implicated in metabolic pathways of biotechnological and pharmaceutical interest), we have recently reported the characterization, purification, crystallization and crystal structure determination of BcZBP , a homohexameric, LmbE-like, zinc-dependent deacetylase from B. cereus . BcZBP is the product of the bc1534 gene, with three, thus far uncharacterized, homologues in B. anthracis sharing sequence identities (at the protein level) of 96%, 28%, and 24%, respectively. Functional studies showed that BcZBP preferentially deacetylates N -acetylglucosamine and diacetylchitobiose, although its specific substrate remains unknown.…”
Section: Introductionmentioning
confidence: 99%